Analysis of trends and features of seaports’ development in the Russian Federation - Z. R. Muradova; A. B. Abakarova (Вестник университета)
The article analyses the economic state and prospects for the development of modern seaports in the context of the development of the transport  infrastructure of the Russian Federation as a key factor in increasing the economic efficiency of public production. A review of the seaports of the Russian Federation of the Russian Federation, which includes 67 ports in five marine pools is presented: the Arctic, the Baltic, the Azov-Black Sea, the  Caspian and the Far East. The main stages of development of the seaports are highlighted and the characteristic features of each marine basin are  noted. The analysis of the economic indicators of the activities of marine ports is carried out: cargo turnover, volume of cargo handling and bulk vessels in the seaports of the Russian Federation. The main problems of the development of seaports in Russia are revealed, the objectives of state regulation and the system of state support are considered. The directions of increasing the competitiveness of seaports in the world market are determined.